Smartwatches in the digital health ecosystem for health monitoring in patients with chronic kidney disease and kidney failure: opportunities and challenges - Jeroen P. Kooman; Maggie Han; Sabine H. Josemans; Joris I. Rotmans; Len Usvyat; Bernard Canaud; Peter Kotanko (American Journal of Physiology-Renal Physiology, 2026)
Smartwatches are widely used by the general population as tools to promote wellness. Modern smartwatches can monitor arterial oxygen saturation, blood pressure, heart rate, arrhythmias, physical activity, sleep patterns, falls, and body composition. In individuals with chronic illnesses, smartwatches may support improved self-care and patient empowerment, support advanced phenotyping by providing digital biomarkers, enable early detection of clinically relevant changes in physiological parameters, and facilitate remote patient monitoring. Patients with chronic kidney disease, particularly those with kidney failure, often experience multiple abnormalities in physiological parameters and body functions. These disturbances may go undetected during routine clinical visits or hemodialysis (HD) treatments, yet they can significantly impact outcomes and may be amendable through therapeutic interventions. Especially when integrated with data from electronic health records and medical devices such as HD machines, smartwatches may be part of a digital ecosystem, supporting personalized precision care and patient empowerment. However, the use of smartwatches in healthcare can also produce false positive signals, which can lead to patient anxiety and potentially increase healthcare utilization and contribute to digital inequity. At present, the potential and challenges of smartwatches in kidney disease are largely unexplored. To fill this gap, this review aims to provide a comprehensive overview of smartwatch-based applications in health monitoring, highlighting both opportunities and limitations in patients with chronic kidney disease and kidney failure. Despite promises for future healthcare implementation, the lack of validation studies for clinical-grade measurements presently still precludes the use of smartwatches for clinical decision-making.